Influence of maturity stages, storage temperatures and durations on chilling injury, antioxidant responses and quality of ginger (Zingiber officinale Roscoe) - Tan, Xue Yi (2017)
Ginger (Zingiber officinale Roscoe) harnesses an incredible healing power for a host of ailments and used as spice throughout the world. It contains bioactive compounds such as phenolics, terpenes, flavonoids and curcumin. However, storage life and usage of ginger is limited as it is susceptible to chilling injury (CI). Storage of rhizomes below 12 ºC causes CI and improper maturity stages at harvest caused reduction of ginger quality, decrease storage life and increase fiber and sprouting of ginger. Thus, the objective of the first experiment was to characterize CI of ginger as affected by maturity stages (7, 9 and 11-months after planting), storage temperatures (5, 15 and 25 ºC) and durations (0, 8, 16, 24 and 32 days). Weight loss due to loss of moisture content was significantly higher in the ginger stored at 25 ºC. Eleven-month ginger stored at 25 ºC showed 192% and 149% higher weight loss than 7 and 9-months ginger, respectively, after 32 days of storage. CI indices as measured by pulp translucency, skin peeling and browning on ginger were severe at 5 ºC, less at 15 ºC while no symptom occurred after 32 days storage at 25 ºC. Browning at 5 ºC storage caused ginger pulp colour changed from yellow to light brown with reduction in pulp firmness. However, the pulp firmness for ginger stored at 15 ºC still maintained after 32 days of storage. There was similar soluble solids concentration peak at storage day 24 and ascorbic acid contents dropped as storage durations were extended for all treatments. Thus, based on the results of the first experiment, 7 and 9-months ginger were selected for the second experiment.